Tracer distribution in legume roots and soluble rhizodeposits over a few weeks after a triple isotope (13C, 15N, 33P) labeling - Stevenel, Pierre; Abiven, Samuel; Frossard, Emmanuel; Idupulapati, Rao; Tamburini, Federica; Oberson, Astrid (Springer, 2025)
Belowground carbon (C), nitrogen (N) and phosphorus (P) inputs by plants via roots and rhizodeposition are key drivers of these elements cycling in soils. Tracing and quantification of rhizodeposition using isotope enrichment techniques is based on assumptions that have not simultaneously been tested for C, N and P. Our objectives were: (i) to compare the elemental and isotopic composition (IC) of roots and soluble rhizodeposits for C, N and P; and (ii) to compare the IC of root segments of different ages to assess the homogeneity of root system labeling. Methods: The legume Canavalia brasiliensis was grown in sand and labeled with 13 C, 15 N and 33 P by using a novel tri-isotope method in two different experiments lasting two (percolate collection) and three weeks (root observation) after labeling. Results: Soluble rhizodeposits were less isotope enriched than roots at each time point, and each element showed a different course over time. The 13 C: 15 N and 13 C: 33 P ratios of rhizodeposits were higher shortly after labeling than at later samplings, highlighting faster transfer of 13 C than 15 N and 33 P into rhizodeposits. Phosphorus fertilizer increased the difference between IC of P in roots and rhizodeposits. Youngest root segments were more isotopically enriched than older segments, again with element specific time course, showing that root segments of different ages differ in IC. Conclusion: Assumptions underlying the quantification of rhizodeposition are not met. Temporal and spatial differences in IC of roots and soluble rhizodeposits are element specific, which needs to be considered in stoichiometric studies.